The Effect of the Weight of Equipment on Muscle Activity of the Lower Extremity in Soldiers - Tobias Lindner; Christoph Schulze; Sandra Woitge; Susanne Finze; Wolfram Mittelmeier; Rainer Bader (The Scientific World Journal)
Due to their profession and the tasks it entails, soldiers are exposed to high levels of physical activity and strain. This can result in overexertion and pain in the locomotor system, partly caused by carrying items of equipment. The aim of this study was to analyse the extent of muscle activity in the lower extremities caused by carrying specific items of equipment. For this purpose, the activity of selected groups of muscles caused by different items of equipment (helmet, carrying strap, backpack, and rifle) in the upper and lower leg was measured by recording dynamic surface electromyograms. Electrogoniometers were also used to measure the angle of the knee over the entire gait cycle. In addition to measuring muscle activity, the study also aimed to determine out what influence increasing weight load has on the range of motion (ROM) of the knee joint during walking. The activity of recorded muscles of the lower extremity, that is, the tibialis anterior, peroneus longus, gastrocnemius lateralis, gastrocnemius medialis, rectus femoris, and biceps femoris, was found to depend on the weight of the items of equipment. There was no evidence, however, that items of equipment weighing a maximum of 34% of their carrier’s body weight had an effect on the ROM of the knee joint.